The suitability of 129SvEv mice for studying depressive-like behaviour: both males and females develop learned helplessness - Chourbaji, Sabine; Pfeiffer, Natascha; Dormann, Christof; Brandwein, Christiane; Fradley, Rosa; Sheardown, Malcolm; Gass, Peter (Behavioural brain research, 2010)
Behavioural studies using transgenic techniques in mice usually require extensive backcrossing to a defined background strain, e.g. to C57BL/6. In this study we investigated whether backcrossing can be replaced by using the 129SvEv strain from which the embryonic stem cells are generally obtained for gene targeting strategies to analyze e.g. depression-like behaviour. For that purpose we subjected male and female 129SvEv mice to two frequently used depression tests and compared them with commonly used C57BL/6 mice. 129SvEv and C57BL/6 mice exhibited differing profiles with regard to locomotion and pain sensitivity. However, in the learned helplessness paradigm, a procedure, which represents a valid method to detect depressive-like behaviour, 129SvEv animals develop a similar level of helplessness as C57BL/6 mice. One great advantage of the 129SvEv animals though, is the fact that in this strain even females develop helplessness, which could not be produced in C57BL/6 mice. In the tail suspension test, both genders of 129SvEv exhibited more despair behaviour than C57BL/6 animals. We therefore suggest that this strain may be utilized in the establishment of new test procedures for affective diseases, since costly and time-consuming backcrossing can be prevented, depressive-like behaviour may be analyzed effectively, and gender-specific topics could be addressed in an adequate way.